Faktor-Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Desa Buru Kaghu Kecamatan Wewewa Selatan Kabupaten Sumba Barat Daya - Enosius Dapa Suda; Engelina Nabuasa; Indriati A. Tedju Hinga (Lontar : Journal of Community Health, 2019)
Diarrhea is the loss of body fluids within 24 hours with the frequency of bowel movements more than three times a day. Number of patients with diarrhea in health centers Teke Tena last three years has risen in 2016 as many as 150 people, in 2017 250 in 2018 328 people. Buru village Kaghu in 2016-2018 had the highest diarrhea patients from four other villages, namely the village Werilolo 17 cases, 40 cases Weebaghe village, village Milla Ate 35 cases, 35 cases Bedu Pasono village, almost every year from 2016 to 2018 outbreak of diarrhea in infants that result in death if not treated quickly. The purpose of this research is to know the factors related to the occurrence of diarrhea in infants in Buru village Kaghu 2019, this type of research is analytic research with, sample of 90 people with a statistical analysis using Chi-Square test. The results of this study indicate that there is a relationship between the mother's knowledge with the incidence of diarrhea in infants (p value = 0.012), there is a correlation between drinking water treatment (p value 0.000), there is a correlation between the availability of latrines (p value = 0.015), there was no relationship between the wash hands with soap and clean water with the incidence of diarrhea in infants (p value = 0.158), there was no relationship between the provision of breastfeeding with the incidence of diarrhea in infants (p value = 0.823), there was no correlation between the cleanliness of the equipment with the incidence of diarrhea in infants (p value 0.652).